SISTEM PEMELIHARAAN DAN STRUKTUR POPULASI SAPI BALI DI DESA SULI, KECAMATAN SALAHUTU, KABUPATEN MALUKU TENGAH - Fredek Rumtily; Godlief Joseph; Abraham Tulalesy (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This research aims to analyze the rearing system and population structure of Bali cattle in Suli Village, Salahutu District, Central Maluku Regency. Data was obtained through surveys, interviews and direct observation, as well as using descriptive methods to describe the characteristics of respondents, rearing systems and livestock population structure. The research results show that the majority of breeders are of productive age, all are men, have secondary education, and have 5-15 years of business experience. The maintenance system implemented is extensive, with the main feed being local forage. The population structure is dominated by mature female cattle, which are important for maintaining reproductive sustainability, while young cattle and calves show good regeneration potential. This research recommends training for farmers regarding fermented feed technology, artificial insemination, and improving management skills. Increasing women's involvement in animal husbandry can also enrich business perspectives and efficiency.